The assumed assimilation of cholesterol by Lactobacilli and Bifidobacterium bifidum is due to their bile salt-deconjugating activity. - Klaver, F A (1993)
To study the mechanism of the propsed assimilation of cholesterol, we cultured various strains of Lactobacillus acidophilus and a Bifidobacterium sp. in the presence of cholesterol and oxgall. During culturing, both cholesterol and bile salts were precipitated. Because of bacterial bile salt deconjugation, no conjugated bile salts were observed in either the culture fluids or the pellets. During incubation, the cell count and optical density decreased. The degree of precipitation of bile salts and of cholesterol was dependent on the culture conditions. If L. acidophilus RP32 was cultured under acidifying conditions, the degree of precipitation of deconjugated bile salts was higher than if the pH was maintained at 6.0. Under acidifying conditions, cholesterol was coprecipitated with the bile salts, whereas in pH-controlled cultures, no coprecipitation of cholesterol was observed. From control experiments with different mixtures of bile salts, it appeared that coprecipitation of cholesterol during culturing was a result of formation of deconjugated bile salts, which have a decreased solubility at pH values lower than 6.0. It is concluded that the removal of cholesterol from the culture medium by L. acidophilus RP32 and other species is not due to bacterial uptake of cholesterol, but results from bacterial bile salt-deconjugating activity.